Effects of novel glucose-lowering drugs on the lipid parameters: A systematic review and meta-analysis. (May 2022) - Dar, Sophia; Siddiqi, Ahmed Kamal; Alabduladhem, Tamim Omar; Rashid, Ahmed Mustafa; Sarfraz, Saba; Maniya, Talha; Menezes, Ritesh G.; Almas, Talal
Abstract: Aim: We aim to evaluate the impacts of sodium-glucose co-transporter 2 inhibitors (SGLT-2), glucagon-like peptide 1 agonist (GLP-1RAs), and dipeptidyl peptidase-four (DPP4) inhibitors on the levels of high-density lipoprotein, low-density lipoprotein, triglyceride and total cholesterol. Methods: The MEDLINE database was searched from inception till October 2021, for randomized controlled trials assessing the effects of sodium-glucose co-transporter two inhibitors (SGLT-2), glucagon-like peptide 1 agonist (GLP-1RAs), and dipeptidyl peptidase-four (DPP4) inhibitors on lipid levels. Results: A total of 57 trials were included in the analysis. Our pooled analysis demonstrates that SGLT-2 inhibitors significantly increase the levels of HDL (WMD = 0.07 mg/dL [0.06 to 0.08], P < 0.00001). SGLT-2 inhibitors were also found to be significantly associated with an increase in the levels of LDL (WMD = 0.11 mg/dL, [0.09–0.13 mg/dL, P < 0.00001). Pooled analysis also demonstrates that SGLT-2 inhibitors significantly reduce the levels of triglyceride (WMD = −0.10 mg/dL, [-0.13 to −0.06], P < 0.00001). Our pooled analysis demonstrates that SGLT-2 inhibitors significantly increased the levels of total cholesterol (WMD = 0.10 mg/dL, [0.06 to 0.15], P < 0.0001), whereas, GLP-1RAs significantly reduced the levels of total cholestrol (WMD = −0.18 mg/dL, [-0.34 to −0.02], P = 0.03). Conclusion: This is the first head-to-head study comparing the effects of 3-novel glucose-lowering agents to lipid parameters. However, more trials are crucial to better understand the impact of glucose-lowering drugs on lipid parameters. Highlights: This systematic review and meta-analysis evaluated the effects of novel glucose lowering agents on the levels of high-density lipoprotein, low-density lipoprotein, triglyceride and total cholesterol. We found that SGLT2 inhibitors show a significant increase in LDL and HDL. More studies are required to assess the effects of DPP4 inhibitors.